2022
DOI: 10.1128/spectrum.00544-22
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Combined with Multiple-Low-Frequency, Low-Intensity Ultrasound To Relieve Osteomyelitis through Sonoantimicrobial Chemotherapy

Abstract: Antibiotic therapy is the first choice for clinical treatment of osteomyelitis, but the formation of bacterial biofilms and the emergence of many drug-resistant strains also create an urgent need to find an alternative treatment to effectively eliminate the infection. Recently, LFLIU has come to be considered a safe and promising method of debridement and antibacterial therapy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Our research team found that EMO can exert anti-inflammatory effects through modulation of the Toll-like receptor 4/nuclear factor kappa-B (TLR4/NF-κB) signaling pathway for the treatment of ulcerative colitis [ 15 ]. In addition, EMO is also widely used in various inflammatory diseases, such as osteomyelitis, pneumonia and nephritis [ 16 , 17 ]. Building on these findings, our previous research delved into the promising anti-inflammatory effects of EMO in the context of CNP.…”
Section: Introductionmentioning
confidence: 99%
“…Our research team found that EMO can exert anti-inflammatory effects through modulation of the Toll-like receptor 4/nuclear factor kappa-B (TLR4/NF-κB) signaling pathway for the treatment of ulcerative colitis [ 15 ]. In addition, EMO is also widely used in various inflammatory diseases, such as osteomyelitis, pneumonia and nephritis [ 16 , 17 ]. Building on these findings, our previous research delved into the promising anti-inflammatory effects of EMO in the context of CNP.…”
Section: Introductionmentioning
confidence: 99%
“…In the anti-infection field, physical LFU can not only enhance the anti-infection ability of antibiotics but also reduce the risk of bacterial antibiotic resistance ( 19 ). Other researchers and we have found that LFU can improve the antibacterial effect of various antibiotics on planktonic and biofilm bacteria in vitro and in vivo , such as MRSA, Pseudomonas aeruginosa , and Klebsiella pneumoniae ( 20 22 ).…”
Section: Introductionmentioning
confidence: 99%